Use of the Single Index Model in Determining Investment Decisions During the Covid-19 Pandemic: Study on IDX30 Index Stocks on the IDX in 2020-2021 - Anwar; Amiruddin Tawe (Economics and Business Journal (ECBIS), 2023)
This study aims to determine stock investment decisions during the COVID-19 pandemic using a single index model. The population in this study is all the shares of companies that are included in the IDX30 market index on the Indonesia Stock Exchange for the 2020-2021 period, namely 40 stocks, while the sample is 39 stocks selected based on purposive sampling technique. Data collection using documentation techniques. Data analysis was carried out using a single index model, starting with collecting the closing stock prices of each to get the optimal portfolio. The results of this study indicate that there are 29 stocks included in the optimal portfolio during the COVID-19 pandemic, namely (ADRO), (ANTM), (ASII), (BBCA), (BBNI), (BBRI), (BBTN), ( BMRI), (BRPT), (BTPS), (CPIN), (ERAA), (EXCL), (INCO), (INKP), (JPFA), (KLBF), (MIKA), (PGAS), (PTPP) , (PWON), (TBIG), (TINS), (TKIM), (TLKM), (TOWR), (UNTR), and (WSKT).